Faktor Risiko yang Berhubungan dengan Kejadian Lesi Prakanker Serviks (IVA+) di Puskesmas Bakunase Kota Kupang Tahun 2019 - Rambu Aji Paremajangga; Honey I. Ndoen; Yuliana R. Riwu (Universitas Nusa Cendana, 2020)
Servical cancer is the most common cancer in women in the world and ranks second most cause of death after cardiovascular disease. Early detection of cervical cancer is done through IVA method. Early detection of servical cancer in Kupang City Health Office in 2017 totaling 1.757 woman and 58 women are positive for cervical precancerous lesions with highest cases in the Bakunase Health Center as many as 38 people. The purpose of this study was to analyze the factors of age at first marriage, habits of changing partners, parity and pathological vaginal history of the occurrence of cervical precancerous lesions (IVA +) in Bakunase Health Center Kupang City in 2019. This type of research is an analytic survey with a case control research design. To analyze the relationship between the variables used the chi square test and the magnitude of risk factors calculated Odds Ratio (OR) values. The results showed that there was a relationship between age at first marriage p = 0.038 (OR = 2.979; 95% CI 1.164-7.622), parity p = 0.021 (OR = 3.322; 95% CI: 1.293-8.538), pathological vaginal discharge p = 0.021 ( OR = 3,375; 95% CI: 1,303-8,744), while the habit of changing sexual partners is not a risk factor associated with the incidence of precancerous cervical lesions p = 0.358 (OR = 4.353; 95% CI 0.463-40.898. Suggestions for Kupang City Bakunase Health Center to conduct counseling about risk factors and dangers of cervical cancer, create an HPV vaccination program and encourage every woman to vaccinate. For women-only communities to avoid risk factors and make periodic early detection for those who have already married.